Mountain...village...home... a B'laan cycle. (Manila Travel time, 1996)
Features the life, art and culture of the B'laan, the indigenous group in South Cotabato.
VHS format.
Susan Calo Medina, host / producer ; Floy Quintos, scriptwriter.
Keywords: B'laan -- Social life and customs; Art, B'laan -- Philippines